Effect of age on perception of eating disorder risk factors in professional volleyball players - Frideres, J. E.; Visiedo, A.; Palao, J. M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2014)
The purpose of this study was to assess professional female volleyball players ́ attitudes toward weight control, diet, and eating disorders with regard to their age. The sample consisted of 41 players from seven teams of the Spanish first division that competed in the National Club Cup. A descriptive, selective, and transversal design was used. The sample was divided into younger and older players for its analysis. The information was obtained from a survey. Players ́ attitudes toward weight control, diet, and eating disorders did not change with regard to their age. The studied players perceived that they had enough knowledge about nutrition and eating disorders. The results show that the coach ́s role as a source of information for athletes has changed. The paper proposes the need to adopt pro-active strategies to minimize the risk of eating disorders in volleyball.